How the reverse supply chain impacts the firm's financial performance: A manufacturer's perspective. Issue 3 (3rd April 2018) - Larsen, Samuel Brüning; Masi, Donato; Feibert, Diana Cordes; Jacobsen, Peter
Abstract : Purpose: Although manufacturers have traditionally viewed reverse supply chain (RSC) activities as a costly nuisance, more recent research has found that the RSC can contribute to the firm's financial performance. The purpose of this paper is to identify how the RSC can contribute to the firm's financial performance and examine the exogenous contingency factors decisive for the contribution's size. Because the exogenous factors are outside the control of the firm's operations and supply chain management, the factors influence the RSC's financial contribution irrespective of managerial policies and design decisions. Design/methodology/approach: The paper applies a systematic literature review using the sequence of planning the review, searching and screening literature, extracting information from the selected literature, and synthesizing and analyzing findings. In total, 112 papers were included. Findings: The study has identified 15 distinct opportunities for RSC-contribution to the firm's financial performance. The study has identified 56 contingency factors. These are related to market segmentation, customer behavior, product design, and the firm's distributor network. The study includes an interrelationship network between factors and the RSC's contribution. Practical implications: For managers, the paper shows how the RSC can increase the firm's financial performance and which contingency factors determine whether operating a RSC will be financially viable if implemented. Originality/value: While extant literature includes several reviews about RSC-related managerial policies and design decisions, this paper contains the very first collection of RSC-contribution opportunities available to manufacturers as well as the first review of exogenous contingency factors.